Cranberry Extract for Symptoms of Acute, Uncomplicated Urinary Tract Infection: A Systematic Review - Oghenekome A. Gbinigie; Elizabeth A. Spencer; Carl J. Heneghan; Joseph J. Lee; Christopher C. Butler (Antibiotics, 2020)
Background: Effective alternatives to antibiotics for alleviating symptoms of acute infections may be appealing to patients and enhance antimicrobial stewardship. Cranberry-based products are already in wide use for symptoms of acute urinary tract infection (UTI). The aim of this review was to identify and critically appraise the supporting evidence. Methods: The protocol was registered on PROSPERO. Searches were conducted of Medline, Embase, Amed, Cinahl, The Cochrane library, Clinicaltrials.gov and WHO International Clinical Trials Registry Platform. We included randomised clinical trials (RCTs) and non-randomised studies evaluating the effect of cranberry extract in the management of acute, uncomplicated UTI on symptoms, antibiotic use, microbiological assessment, biochemical assessment and adverse events. Study risk of bias assessments were made using Cochrane criteria. Results: We included three RCTs (n = 688) judged to be at moderate risk of bias. One RCT (n = 309) found that advice to consume cranberry juice had no statistically significant effect on UTI frequency symptoms (mean difference (MD) −0.01 (95% CI: −0.37 to 0.34), p = 0.94)), on UTI symptoms of feeling unwell (MD 0.02 (95% CI: −0.36 to 0.39), p = 0.93)) or on antibiotic use (odds ratio 1.27 (95% CI: 0.47 to 3.43), p = 0.64), when compared with promoting drinking water. One RCT (n = 319) found no symptomatic benefit from combining cranberry juice with immediate antibiotics for an acute UTI, compared with placebo juice combined with immediate antibiotics. In one RCT (n = 60), consumption of cranberry extract capsules was associated with a within-group improvement in urinary symptoms and Escherichia coli load at day 10 compared with baseline (p < 0.01), which was not found in untreated controls (p = 0.72). Two RCTs were under-powered to detect differences between groups for outcomes of interest. There were no serious adverse effects associated with cranberry consumption. Conclusion: The current evidence base for or against the use of cranberry extract in the management of acute, uncomplicated UTIs is inadequate; rigorous trials are needed.